The antibacterial activity and therapeutic potential of the amphibian-derived peptide TB_KKG6K - Cristina Schöpf; Magdalena Knapp; Jakob Scheler; Débora C. Coraça-Huber; Alessandra Romanelli; Peter Ladurner; Anna C. Seybold; Ulrike Binder; Reinhard Würzner; Florentine Marx (mSphere)
ABSTRACT Antimicrobial peptides (AMPs) have great potential to be developed as topical treatments for microbial infections of the skin, including those caused by the gram-positive human pathogen Staphylococcus aureus. Among the AMPs, temporin B (TB) is of particular interest. This 13-amino-acid-long cationic peptide is secreted by the granular glands of the European frog Rana temporaria and represents a primary line of defense against invading pathogens. The objective of this study was to investigate the antibacterial efficacy and the mode of action of the synthetic TB analog, TB_KKG6K, in a drug-resistant clinical isolate of S. aureus and assess the peptide’s tolerance and curative potential in an in vitro infection model using three-dimensional human epidermis equivalents (HEEs). The results revealed a high bactericidal efficacy of TB_KKG6K at low micromolar concentrations. The peptide perturbed the bacterial cell membrane integrity by permeabilization and depolarization. TB_KKG6K showed no toxicity in the invertebrate mini-host model Galleria mellonella and a high level of tolerance when topically applied in HEEs. Importantly, the therapeutic potential of TB_KKG6K was confirmed in HEEs infected with S. aureus. The topical application of TB_KKG6K significantly reduced the bacterial load and lowered the pro-inflammatory response in the infected HEEs. These findings reinforce the antibacterial potential and therapeutic efficacy of TB_KKG6K against S. aureus infection, particularly in the context of a cutaneous infection.IMPORTANCEThe emergence of multidrug-resistant bacteria has rendered the exploration of novel therapeutic treatment strategies a pivotal area of research. Among the most promising candidates are amphibian-derived antimicrobial peptides (AMPs), which are ideal for the development of novel drugs due to their multifaceted mode of action. Extensive studies have been conducted on these peptides over the last decade, resulting in the development of temporin B (TB) peptide analogs that have undergone modifications to their primary sequence. These modified analogs have demonstrated enhanced antibacterial and antifungal efficacy, while exhibiting reduced hemolytic activity. TB_KKG6K has the potential to be a promising candidate for topical treatments due to its small size and high antimicrobial activity against pathogens of the human skin. In particular, it demonstrated efficacy against Staphylococcus aureus, a skin commensal that can become an opportunistic pathogen, causing a range of infections from minor skin infections to life-threatening diseases such as bacteremia and sepsis.